Own the Podium - 2010. Final report. With recommendations of the independent task force for winter NSOs and funding partners - Allinger, C. P.; Allinger, T. (Speedskating Canada, 2004)
Canadian sport took a giant leap forward, February 2, 2004, in Calgary when the key players in winter sport set the lofty goal of becoming the #1 nation at the 2010 Olympic Winter Games in Vancouver. All winter National Sport Organizations (NSOs), the Canadian Olympic Committee (COC), Canadian Paralympic Committee (CPC), Sport Canada, Calgary Olympic Development Association (CODA), the Vancouver Organizing Committee for the 2010 Olympic and Paralympic Winter Games (VANOC), and 2010 LegaciesNow dubbed the vision, "Own the Podium -2010" (OTP), and set a goal for Canada to win 35 medals at the 2010 Olympic Winter Games. The COC took a lead role in coordinating the project and appointed an Independent Task Force while the winter NSOs approved a steering committee to represent all winter sports. The mandate of the task force was to determine if and how Canada can win over 35 medals at the 2010 Olympic Winter Games in Vancouver. The task force examined the following: 1. Prediction of Medals in 2010 2. Reaching Canada`s projected medal count for 2010 3. Sport technical reviews for 2010 4. Tiering of sports and funding recommendations 5. Strategy for Implementation of "Own the Podium - 2010".